Anti-Prokineticin1 Suppresses Liver Metastatic Tumors in a Mouse Model of Colorectal Cancer with Liver Metastasis - Hiroko Kono; Takanori Goi; Takayuki Matsunaka; Kenji Koneri (Current Issues in Molecular Biology, 2023)
Multidisciplinary treatment for colorectal cancer (CRC) has undergone significant advances, and molecularly targeted drugs have substantially improved patient prognosis. However, one problem with current molecularly targeted therapeutics is that they must be used in combination with anticancer agents. New molecular targeted therapies that can be used alone are needed. We have previously identified prokineticin1 (PROK1) factor as a therapeutic potential target for CRC. PROK1 factor is involved in the angiogenesis of tissues surrounding CRC tumors. Additionally, PROK1 receptors 1 and 2 are expressed in CRC cell lines, playing roles in cell proliferation via an autocrine mechanism and in the signaling system. In this study, a liver metastasis mouse model was developed using human colorectal cancer cell lines, and mice were divided into anti-PROK1 antibody administration and control groups. Mice were treated intraperitoneally with antibodies or phosphate-buffered saline (control) every three days. The number, size, and cell proliferation ability of metastatic lesions were analyzed. Our results suggested that the number, size, and cancer cell proliferation ability of metastatic lesions decreased, and the survival time significantly increased in the antibody-treated group compared to those in the control group. Thus, the anti-PROK1 antibody therapy suppressed the cell proliferation ability of liver metastatic lesions in a CRC mouse model, suggesting its potential as a novel treatment strategy.